RANCANGAN ALAT PEMBUAT MINUMAN KOPI OTOMATIS MENGGUNAKAN MIKROKONTROLER MCS51. - Kalsum, Toibah Umi; Ginta, Prama Wira; Septohadi, Mardian (Jurnal Media Infotama, 2012)
Draft Tool Makers Automatic Coffee Beverage Using MCS51 microcontroller is an activity whose function is to design tools to make coffee drinks maker. This tool uses LDR light sensor to detect the presence of the cup, and use the stepper motors, valves electrically as supporting componentstocompletetheinstrument. The results showed an automatic coffee maker works. Menunjukkn that the test results when there is a cup placed under the faucet, there will be a tool of action is the sugar container tilted to pour the sugar, then coffee container tilted to pour coffee, water, and cups and move left to right to stir the sugar and coffee in the cup. This tool can be operated manually or by computer control, and can also operateautomatically.